Modelling of renewable gas and renewable liquid fuels in future integrated energy systems. (15th June 2020) - Bramstoft, Rasmus; Pizarro-Alonso, Amalia; Jensen, Ida Græsted; Ravn, Hans; Münster, Marie
Highlights: Novel modelling framework allow spatiotemporal optimisation of energy systems. Co-simulating regional power market model and local biomass and district heat model. New detailed spatial optimisation of renewable gas and fuel production. PtX shows promising economic-viability in the future. Excess heat from biorefineries is efficiently used for district heating. Abstract: This study conducts an integrated energy system assessment to evaluate pathways for using locally distributed sustainable biomass resources in the conversion to renewable gas and liquid biofuels in future integrated energy systems. A modelling framework with a detailed spatiotemporal representation is used, optimising the usage and transportation of local biomass resources for producing renewable gas and renewable liquid fuels through the OptiFlow model, along with the comprehensive power and district heating model Balmorel, integrating short-term dynamics in the long-term planning horizon. Results for a fossil-independent Danish energy system by 2050 show that production of bio-jet fuel in Denmark would impose high pressure on national biomass resources. Electrofuels, such as biomethanol, have economic viability and promising potentials. The results regarding renewable gas production show that anaerobic co-digestion of a mixed feedstock to produce biogas, which is further upgraded to biomethane using water scrubbing for CO2 removal, would be the preferred option. Biorefineries are located near larger cities to benefit from economy of scale and access to large district heating networks, as excess heat from biorefineries could supply up to 21% of the national district heating demand. On the contrary, biogas plants would be located in the countryside, as the costs of transporting manure are a determining factor. Therefore, our study provides a novel modelling approach, which enables optimisation of geographical distributed resources for renewable gas and liquid fuel production, while taking synergies across energy vectors in account.